Tindak Tutur Ilokusi Komisif Sajrone Film Jayadi 2020 Anggitane Hajar Pamuji (Tintingan Pragmatik) - Alfionita Herminda; Udjang Pairin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Commissive illocutionary speech acts are a type of speech act that speakers understand to bind themselves to take action in the future. Commissive illocutionary speech acts aim to provide information to their speech partners. The research method used in this study uses a qualitative descriptive method. This method is used to examine natural objects and also describe an image or video systematically. In this study, the researcher conducted a film study taken from YouTube, entitled "Jayadi 2020" by Hajar Pamuji. Where the film tells the story of a true story behind the election of the village head. The technique used for research is the data collection technique. The results of the study of commissive illocutionary speech acts from the film Jayadi 2020 are in the form of promising, threatening, offering, ability, vows, and also refusing.